Opacity and risk-taking: Evidence from Norway - Jin Cao; Ragnar Enger Juelsrud (Norges Bank, 2020)
This paper investigates how balance sheet opacity affects banks' risk-taking behavior. We measure bank balance sheet opacity according to two metrics: the ratio of available-for-sale (AFS) securities and the ratio of off-balance sheet items. We show that balance sheet opacity is positively correlated with realized bank risk. Specifically, banks with more AFS securities have lower realized risk, while banks with more off-balance sheet items have higher realized risk. The correlation between opacity and risk depends on both macroeconomic variables and bank characteristics. The positive relationship between bank opacity and bank risk is weaker for better capitalized banks and banks that are subject to more market discipline. The relationship is also weaker during periods of favorable market conditions. Motivated by this analysis, we then investigate how regulation affects bank opacity. We show that higher capital requirements reduce bank opacity and bank risk through a portfolio rebalancing channel.
hdl:11250/2690085
Keywords: G21; G23; G28; 330; Opacity; Transparency; Available-for-sale securities; Off-balance sheet items; Risktaking